Mercury Toxicity and Detection Using Chromo-Fluorogenic Chemosensors - Vinita Bhardwaj; Valeria M. Nurchi; Suban K. Sahoo (MDPI AG, 2021)
Mercury (Hg), this non-essential heavy metal released from both industrial and natural sources entered into living bodies, and cause grievous detrimental effects to the human health and ecosystem. The monitoring of Hg2+ excessive accumulation can be beneficial to fight against the risk associated with mercury toxicity to living systems. Therefore, there is an emergent need of novel and facile analytical approaches for the monitoring of mercury levels in various environmental, industrial, and biological samples. The chromo-fluorogenic chemosensors possess the attractive analytical parameters of low-cost, enhanced detection ability with high sensitivity, simplicity, rapid on-site monitoring ability, etc. This review was narrated to summarize the mercuric ion selective chromo-fluorogenic chemosensors reported in the year 2020. The design of sensors, mechanisms, fluorophores used, analytical performance, etc. are summarized and discussed.